The Effect of Adding Graphite on the Structural and Mechanical Properties of Titanium Carbide (Journal of University of Babylon for Engineering Sciences, 2018)
The advances ceramics have many applications such as aerospace, refectory, medical, electronic,…etc. In this work, the preparation of  titanium carbide by  using powder metallurgy technique  from titanium and graphite  has been investigated with different weight percentages are  ((86:14),(83:17),(80:20) and (77:23)) wt.%  titanium and graphite respectively. Titanium carbide was formed at (1200°C) for (8hr). The mechanical properties (microhardness,  compression strength and wear rate) and characterization (SEM and XRD)  of titanium carbide samples were studied. The  results  found that the best  mechanical properties for titanium carbide samples prepared at (80:20) wt.%  titanium and graphite respectively.